Direct Foreign Investment and Demographic Policy in the Russian Far East. / Inversión extranjera directa y política demográfica en el Extremo Oriente de Rusia - Gordyachkova, Olga V.; Rotar, Tatyana S.; Danilova, Larissa I. (Utopía y Praxis Latinoamericana)
ABSTRACT The article deals with the problem of attracting foreign direct investment to the economy of the Russian Far East, which is the priority area of the country’s socio-economic strategy. The results show a stable dynamic of foreign direct investment despite economic sanctions imposed on Russia. The key challenges in the development of the Far Eastern region are the quality of labor and its availability and profitability of enterprises. The article outlines the main mechanisms of realizing the demographic policy, which have been proposed in 2018, as well as measures aimed at increasing the profitability of enterprises in the region. RESUMEN El artículo aborda el problema de atraer la inversión extranjera directa a la economía del Extremo Oriente ruso, que es la esfera prioritaria de la estrategia socioeconómica del país. Los resultados muestran una dinámica estable de inversión extranjera directa a pesar de las sanciones económicas impuestas a Rusia. Los desafíos clave en el desarrollo de la región del Extremo Oriente son la calidad de la mano de obra y su disponibilidad y rentabilidad de las empresas. El artículo describe los principales mecanismos de realización de la política demográfica, que se han propuesto en 2018, así como las medidas destinadas a aumentar la rentabilidad de las empresas en la región.